2003
DOI: 10.1074/jbc.m210762200
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational Secretion of Fusion Proteins in the Halophilic Archaea Haloferax volcanii

Abstract: Although protein secretion occurs post-translationally in bacteria and is mainly a cotranslational event in Eukarya, the relationship between the translation and translocation of secreted proteins in Archaea is not known. To address this question, the signal peptideencoding region of the surface layer glycoprotein gene from the Haloarchaea Haloferax volcanii was fused either to the cellulose-binding domain of the Clostridium thermocellum cellulosome or to the cytoplasmic enzyme dihydrofolate reductase from H. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 44 publications
(57 reference statements)
0
46
0
Order By: Relevance
“…Examples of both postand cotranslational translocation have been found in Archaea. Chimeric signal sequence-bearing reporter proteins are secreted posttranslationally from transformed Haloferax volcanii cells (179). In addition, Haloferax volcanii has been reported to posttranslationally insert a chimeric protein containing the multispanning membrane protein bacterio-opsin (318).…”
Section: Archaeal Signal Sequencesmentioning
confidence: 99%
“…Examples of both postand cotranslational translocation have been found in Archaea. Chimeric signal sequence-bearing reporter proteins are secreted posttranslationally from transformed Haloferax volcanii cells (179). In addition, Haloferax volcanii has been reported to posttranslationally insert a chimeric protein containing the multispanning membrane protein bacterio-opsin (318).…”
Section: Archaeal Signal Sequencesmentioning
confidence: 99%
“…In studies involving Haloferax volcanii cells transformed to express chimeric proteins bearing the signal peptide of a native exported protein fused to different reporters, it was shown that protein synthesis and secretion need not be coupled events. 22 In contrast, kinetic radiolabelling approaches revealed the co-translational insertion of the N-terminal portion of the Halobacterium salinarum membrane protein bacterioopsin. 23 Moreover, earlier studies reporting co-sedimentation of SRP (7 S) RNA and bacterioopsin mRNA with membrane-bound polysomes, together with puromycin-induced release of the SRP RNA from the polysomes, 24 as well as more recent studies addressing SRP in H. volcanii 25,26 and other archaeal species, 27 -31 lend further support for the existence of a co-translational mode of protein translocation in Archaea.…”
Section: Introductionmentioning
confidence: 99%
“…In Eukarya, SRP is known to couple protein synthesis to protein translocation at the ER membrane (2), whereas membrane protein insertion involves translocon-bound ribosomes (45). Still, examples of post-translational protein translocation in Archaea have been reported (15). Thus, it is tempting to speculate that archaeal protein translocation involves post-translational secretion and co-translational membrane protein insertion.…”
Section: Discussionmentioning
confidence: 99%
“…The changed membrane protein profile of the transformed cells, relative to the background strain, could reflect the biosynthesis of components involved in post-translational translocation or other proteins in response to this compensatory action. Indeed, post-translational secretion and membrane-protein insertion have been reported to occur in H. volcanii (15,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation